(untitled) (Law, State and Telecommunications Review, 2023)
We are delighted to include articles on self-regulatory initiatives in the field of interactive advertising in Spain and the European Union; the content of the right to internet access under the perspective of the Mexican Constitution; the introduction of artificial intelligence into the Ukrainian Justice System considering international experience; civil liability and the use of artificial intelligence in medical activities in Portugal; intellectual property rights concerning objects created by artificial intelligence in Ukraine; forensic identification of people from video materials in Ukraine; the impact of telematic media on the communication between parents and children in Chile, especially after the mobility restrictions derived from Covid-19; comparative analyses of electronic transactions regulation and criminal offenses in the field of informatization and communications in Kazakhstan; general features of legal regulation of artificial intelligence in the field of Intellectual Property Law; initiatives to counter fake news in India using artificial intelligence and algorithms; and the evolution and regulation of telecommunication in India.